A traceless variant of the Johnson-Segalman viscoelastic model - Pires, Marília (2017)
A traceless variant of the Johnson-Segalman viscoelastic model is presented. The viscoelastic extra stress tensor is de composed into its traceless (deviatoric) and spherical parts, leading to a reformulation of the classical Johnson-Segalman model. The equivalente of the two models is established comparing model predictions for simple test cases. The new model is validated using several 2D benchmark problems.The structure and behavior of the new model are discussed.